Employee ownership in Jamaica - Panton, D; David Panton (1999)
﻿ In March 1994, the Jamaican Parliament passed the Employee Share Ownership Plan (ESOP) Act, to facilitate widespread employee share ownership by granting tax incentives to companies that offer shares to their employees (GOJ 1994). The primary aims of the legislation were to (a) strengthen Jamaica's economy by enabling workers to acquire an ownership stake in their employer and (b) improve the economic performance of Jamaican companies by encouraging employees to identify more closely with the goals of their employers (GOJ 1993). Former Jamaican Prime Minister Michael Manley, who introduced the ESOP legislation into Parliament, explained that organizational rather than ideological goals were the primary aims of the legislation. He explained that "in due course larger goals such as broadening the base of ownership and giving workers a wider stake in the national economy will also be achieved through ESOPs. But the first objective must be to increase productivity at the company level" (Manley 1995:17). Prior to the passage of this legislation, several employee ownership schemes had been implemented by Jamaican companies on a limited and ad hoc basis without the support of legislation (GOJ 1993). Despite the introduction of these earlier schemes, however, the concept of employee ownership is still a new one to Jamaica and little research has been conducted on how the pre-legislation employee ownership schemes were implemented or how they affected the implementing companies. Although consultants to the government examined these companies and used them as models in drafting the ESOP legislation, the consultants performed no academic studies to examine the organizational impact of the employee share schemes (Golding; Maharaj Interviews). Similarly, several academic studies have been conducted on employee ownership in the US, the UK, and a few other countries, but no formal academic studies of employee ownership have been conducted in Jamaica. These omissions are unfortunate given the interest in ESOPs expressed by the Jamaican government and the desired political, economic, and organizational effects of introducing employee ownership schemes. [Please see pdf. for full abstract.]